INNOVATIVE APPROACHES TO TEACHING INFORMATION TECHNOLOGY IN EDUCATION (Journal of Universal Science Research, 2023)
In this article, innovative approaches, methods, technologies and solutions to current problems are reflected in the teaching of information technology in education .